PENGARUH PERBEDAAN UMUR PANEN TERHADAP PRODUKTIVITAS (produksi segar, produksi bahan kering, serta proporsi daun dan batang) HIJAUAN Indigofera zollingeriana - Prayoga, Ibnu Kesuma; Fathul, Farida; Liman, Liman (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2018)
This research aims to know the effect of harvest age differences on productivity (fresh production, dry matter production, proportion of leaves and stems) and to know the age of harvest with optimal productivity of forage Indigofera zollingeriana. This research was conducted in May until August 2017 in Purwodadi Village, Pringsewu District, Lampung and the dry matter proximate analysis was conducted at the Nutrition and Feeding Laboratory, Livestock Department, Lampung University. It consisted of harvest age at 40 days (P40), 55 days (P55), 70 days (P70), and 85 days (P85). The design used in this experiment is, Completely Randomized Design. The variables in this research are, 1. fresh production; 2. dry matter production; 3. the proportion of leaves and stems of forages Indigofera zollingeriana. The data obtained were analyzed by analysis of variance at 1% and then test using Polynomial orthogonal. The results showed that the difference of harvest age had a very real effect (P<0,01) on productivity (fresh production, dry matter production, proportion of leaves and stems) forage Indigofera zollingeriana. In the 40 to 85 days age range, the following equations are made, fresh production : ŷ(ton/ha) = 1,65 + 0,049x [40:85 days]; dry matter production : ŷ(ton/ha) = 0,038 + 0,005x [40:85 days]; the proportion of leaves : ŷ(%) = 80,69 – 0,19x [40:85 days]; and the proportion of stems : ŷ(%) = 19,31 + 0,19x [40:85 days]. Keywords: harvest age, fresh production, dry matter production, proportion of leaves and stems, forage Indigofera zollingeriana.